Functional Nanoparticles for Tumor Penetration of Therapeutics - Yu-Lin Su; Shang-Hsiu Hu (MDPI AG, 2018)
Theranostic nanoparticles recently received great interest for uniting unique functions to amplify therapeutic efficacy and reduce side effects. Despite the enhanced permeability and retention (EPR) effect, which amplifies the accumulation of nanoparticles at the site of a tumor, tumor heterogeneity caused by the dense extracellular matrix of growing cancer cells and the interstitial fluid pressure from abnormal angiogenesis in the tumor inhibit drug/particle penetration, leading to inhomogeneous and limited treatments. Therefore, nanoparticles for penetrated delivery should be designed with different strategies to enhance efficacy. Many strategies were developed to overcome the obstacles in cancer therapy, and they can be divided into three main parts: size changeability, ligand functionalization, and modulation of the tumor microenvironment. This review summarizes the results of ameliorated tumor penetration approaches and amplified therapeutic efficacy in nanomedicines. As the references reveal, further study needs to be conducted with comprehensive strategies with broad applicability and potential translational development.